Gene‐specific criteria for PTEN variant curation: Recommendations from the ClinGen PTEN Expert Panel. Issue 11 (11th October 2018) - Mester, Jessica L.; Ghosh, Rajarshi; Pesaran, Tina; Huether, Robert; Karam, Rachid; Hruska, Kathleen S.; Costa, Helio A.; Lachlan, Katherine; Ngeow, Joanne; Barnholtz‐Sloan, Jill; Sesock, Kaitlin; Hernandez, Felicia; et al.
Abstract: The ClinGen PTEN Expert Panel was organized by the ClinGen Hereditary Cancer Clinical Domain Working Group to assemble clinicians, researchers, and molecular diagnosticians with PTEN expertise to develop specifications to the 2015 ACMG/AMP Sequence Variant Interpretation Guidelines for PTEN variant interpretation. We describe finalized PTEN ‐specific variant classification criteria and outcomes from pilot testing of 42 variants with benign/likely benign (BEN/LBEN), pathogenic/likely pathogenic (PATH/LPATH), uncertain significance (VUS), and conflicting (CONF) ClinVar assertions. Utilizing these rules, classifications concordant with ClinVar assertions were achieved for 14/15 (93.3%) BEN/LBEN and 16/16 (100%) PATH/LPATH ClinVar consensus variants for an overall concordance of 96.8% (30/31). The variant where agreement was not reached was a synonymous variant near a splice donor with noncanonical sequence for which in silico models cannot predict the native site. Applying these rules to six VUS and five CONF variants, adding shared internal laboratory data enabled one VUS to be classified as LBEN and two CONF variants to be as classified as PATH and LPATH. This study highlights the benefit of gene‐specific criteria and the value of sharing internal laboratory data for variant interpretation. Our PTEN‐specific criteria and expertly reviewed assertions should prove helpful for laboratories and others curating PTEN variants. Abstract : The ClinGen PTEN Expert Panel (EP) includes clinicians, researchers, and molecular diagnosticians with PTEN ‐related expertise who collaborated to create PTEN ‐specific variant classification criteria using the framework of the 2015 ACMG/AMP Sequence Variant Interpretation Guidelines. This article describes the development of these criteria and their application for variant classification. These PTEN ‐specific criteria and the classification assertions made by the EP should prove helpful for laboratories and others who curate PTEN variants.